Program Edukasi Asuhan Kebidanan Untuk Mencegah Komplikasi Kehamilan Pada Ibu Dengan Pernikahan Dini - Zumrotul Ula; Fara Khansa Azizah; Andi Hartati; Cakrawati R (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Early marriage remains a significant public health problem in Indonesia, particularly in rural areas. Pregnancy at a young age increases the risk of complications such as anemia, preeclampsia, premature birth, low birth weight (LBW), and even maternal and infant mortality. Lack of knowledge about midwifery care and reproductive health is a major factor in the high risk of these complications. This community service program aims to increase mothers' knowledge and awareness of early marriage through integrated midwifery care education. The program was conducted with 40 pregnant women aged 15–20 years in the target area. Methods used included direct counseling, prenatal care demonstrations, simple antenatal check-ups, educational materials, and evaluation through pre- and post-tests. Results showed a significant increase in mothers' knowledge regarding pregnancy danger signs, nutrition, prenatal care, and the importance of regular check-ups. The average knowledge score increased from 54.2 to 88.5. Eighty-five percent of participants reported behavioral changes in ANC visits and iron tablet consumption. This program has proven effective in increasing the capacity of young mothers to prevent pregnancy complications. Sustainable interventions are essential to minimize the long-term impact of early marriage on maternal and child health.